Late presentation of vitamin D-dependent rickets. Issue 12 (December 1980) - Cowen, J; Harris, F
Abstract : An 8 1/2-year-old girl presented with rickets. This had developed despite a normal diet and in the absence of symptoms, signs, or laboratory evidence of malabsorption, hepatic or renal disease. The rickets healed with physiological doses of 1-alpha-hydroxy-cholecalciferol. It is suggested that this case provides evidence for genetic and metabolic heterogeneity in vitamin D-dependent rickets.